Reality Show Production Strategy to Attract the Audience: Case Study of NET TV Siap Bos Program - Nauzal, Achmad; Setiawati, Titin (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
This study uses a qualitative descriptive, data collection techniques are observation, documentation, and in-depth interviews with the production team and the audience. Using the constructivism paradigm and study of organizational communication in production teams through the organizational control theory in broadcasting institutions. In the midst of the efforts of television stations to survive amidst the onslaught of online media, the strategy of the production team for the Siap Boss program includes planning, production, execution and evaluation, based the strtagy to ratings and shares in order to obtain a good television program. The strategy for the production team for the Siap Boss program focuses on the process of brainstorming, modifying and developing content by evaluating previous episodes, conducting research and coordinating them with the hosts, packaging the program with the addition of a creative strategy in the form of graphic editing as a unique characteristic of the Siap Boss program, so that it is interesting, not monotonous. The strategy aimed to achieve the objectives of the Siap Bos production team in attracting the audience.